Measurement of fetal atrioventricular time intervals: A comparison of 3 spectral Doppler techniques - Sanitra Anuwutnavin (2019)
© 2018 John Wiley & Sons, Ltd. Objective: To establish nomograms for fetal atrioventricular (AV) time intervals assessed by 3 different pulsed-wave Doppler techniques: left ventricular inflow and outflow tracts (LV in/out), superior vena cava and ascending aorta (SVC/AA), and pulmonary artery and pulmonary vein (PA/PV). Methods: A cross-sectional study was performed in 311 normal fetuses divided into 5 groups between 16 and 38 weeks. Pulsed-wave Doppler-derived AV intervals were measured by interrogation of flow in LV in/out, SVC/AA, and PA/PV. Linear regression analyses were performed to examine correlations with gestational age (GA) and fetal heart rate (FHR). Intraclass correlation coefficients for reproducibility of each method were compared. Results: Pulmonary artery and pulmonary vein revealed the longest mean AV time intervals (P <.001). The AV intervals in all methods were positively correlated with GA (R 2  = 0.20-0.36; P <.001) and negatively correlated with FHR (R 2  = 0.09-0.19; P <.001). The SCV/AA time intervals demonstrated the weakest influence of FHR. For LV in/out, SVC/AA, and PA/PV, intraobserver and interobserver reliability coefficients showed excellent agreements (all intraclass correlation coefficients ≥ 0.80). Conclusion: All pulsed-wave Doppler-derived AV time intervals increased with advancing GA and decreased with increasing FHR. Fetal AV interval measurements can be obtained in a clinically viable fashion with excellent reproducibility.